2010
DOI: 10.1177/097340821000400219
|View full text |Cite
|
Sign up to set email alerts
|

The Earth Charter and the ESDinds Initiative

Abstract: This descriptive report outlines an innovative project in which Earth Charter International is actively involved. The project aims to develop approaches, indicators and tools for Civil Society Organisations (CSOs) to be able to measure values-based aspects and impacts of their work at the project level.Dimity Podger is Research Fellow at the University of Brighton, UK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…An evaluation of the Noonkodin program was recently initiated, using a values-based indicators approach (Podger et al 2010, Burford et al 2013 to compare the values, attitudes, and behavior of Noonkodin students with those of students at two mainstream secondary schools. Preliminary results are encouraging, suggesting that Noonkodin students are learning to challenge stereotypes, think critically, and construct new knowledge to address sustainability challenges.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An evaluation of the Noonkodin program was recently initiated, using a values-based indicators approach (Podger et al 2010, Burford et al 2013 to compare the values, attitudes, and behavior of Noonkodin students with those of students at two mainstream secondary schools. Preliminary results are encouraging, suggesting that Noonkodin students are learning to challenge stereotypes, think critically, and construct new knowledge to address sustainability challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Although Arnold and Fernandez-Gimenez (2007:483) use the term "quality" to encompass both participation breadth and "the sincerity and thoughtfulness of participant engagement", we suggest that quality is a separate dimension from breadth and the two should not be conflated. Intangible attributes such as sincerity are difficult to quantify; although some progress has been made recently in developing methodologies for measuring ethical and spiritual values (Podger et al 2010, Burford et al 2013), a detailed examination of such approaches is beyond the scope of this paper. Thus, without diminishing the importance of sincerity and thoughtfulness, we present an initial conceptual framework focusing on the tangible dimensions of depth, scope, and breadth.…”
Section: Dimensions Of a Participation Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…We will do this by bringing in a specialized values-based approach from social design which reports being able to crystallize the shared values of local groups (Podger et al, 2013) thereby "making the invisible visible" (Burford et al, 2015) and consequently developing them into local indicators (Burford et al, 2013b). The general approach, known colloquially as 'WeValue', was originally designed to amplify the voice of civil society groups (Podger et al, 2010), and has since been used to assist environmental groups to evaluate their goals on their own terms (Harder et al, 2014) and has been used across scales and scaled up (Podger et al, 2016) showing its potential for transferability. Ongoing studies have confirmed the validity to local groups of representative proto-indicators of their crystallized 'in-situ'…”
Section: Current Challenges For Social Indicatorsmentioning
confidence: 99%
“…The case study presented here explores an approach from another field that shows potential to help with these challenges through a rather different pathway. The values-based approach known as WeValue was initially developed in 2007-8 (Podger, 2010) to help informal and civil society groups to better articulate the intangible, values-based aspects of their work which were important to them, in their own terms. This was to support them in having a stronger voice about their central aims, and thus to remain grounded in their own values when communicating and negotiating with external evaluators and agencies.…”
Section: Introductionmentioning
confidence: 99%